Automotive mechatronics: a green technology? - Sophian, Ali (2016)
In this presentation, an introduction to mechatronics and its applications in automotive systems will be presented. An attempt will be made to show how mechatronics has been used in various systems that help build modern vehicles that have to meet increasingly stringent environmental regulations. The presentation will be based on both author's experience and some literature study